Does exposure to sexual defeat and prenatal stress result in an inherited predisposition to PTSD in rat offspring? - Mc Donald, Chloe Helen (Stellenbosch : Stellenbosch University, 2025)
Mc Donald, C. H. 2025. Does Exposure to Sexual Defeat and Prenatal Stress Result in an Inherited Predisposition to PTSD in rat Offspring? Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/ae7d220f-e2cf-4231-818a-ff684af63737